Pengaruh Luas Lahan, Harga Global dan Jumlah Produksi terhadap Volume Ekspor Kakao di Indonesia - Gede Rendi Pratama; I Nyoman Wahyu Widiana (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
This study aims to analyze the influence of land area, global cocoa prices, and production volume on Indonesia's cocoa export volume. Cocoa is one of the leading plantation commodities that significantly contributes to the country's foreign exchange and plays an important role in the national economy. However, Indonesia's cocoa export volume has experienced considerable fluctuations over the years due to various internal and external factors, including climate change, international price dynamics, and domestic productivity levels. This research uses time series data spanning 30 years, from 1994 to 2023, obtained from official sources such as the Central Bureau of Statistics (BPS) and international publications. The data were analyzed using multiple linear regression to determine the extent to which each independent variable influences the dependent variable, namely the volume of cocoa exports. The results of the analysis show that only the production volume variable has a statistically significant effect on Indonesia's cocoa export volume. Meanwhile, land area and global cocoa prices do not show a significant influence. These findings suggest that increasing cocoa export volume is more strongly determined by the amount of production available for the international market rather than by the expansion of land area or global price fluctuations. In other words, even if cocoa prices are high or land is expanded, exports will not necessarily increase without improvements in productivity and output. Therefore, strategies for developing Indonesia’s cocoa sector should prioritize enhancing farmer productivity, improving cultivation technology, and increasing efficiency in post-harvest and distribution systems. This study is expected to serve as a reference for policymakers in formulating effective strategies to support the growth of Indonesia’s cocoa exports and strengthen the competitiveness of the national cocoa industry in the global market. Future efforts should focus on sustainable production practices and value-added processing to ensure long-term benefits for all stakeholders involved in the cocoa supply chain.